Persepsi Orang Tua terhadap Remaja Putus Sekolah - Nofrialdi Nofrialdi (Indonesian Journal of Counseling and Development, 2021)
The number of teenagers who drop out of school in Jorong Kampung Baru, South Solok Regency is not only from the teenagers themselves but also from their parents. This is caused by the lack of attention, the poor response of parents to adolescents who go to school and the encouragement from parents to continue their children's education to a higher level. The objectives to be achieved in this study are to describe parents' perceptions of education, parents' perceptions of teenagers dropping out of school and the factors of teenagers dropping out of school. This study uses field research methods, in the form of descriptive field research. The informants of this study were parents of high school dropout teenagers in Jorong Kampung Baru, South Solok Regency. The data was obtained through observation and in-depth interviews